Study the effect of fish on the optical properties of CuO membranes prepared in a way that thermal spraying chemical (Baghdad Science Journal, 2025)
In this research study the effect of fish on the properties optical films thickness 1200-1800 and calculated energy gap Basra direct transport permitted and forbidden to membranes and urged decreasing values ??of Optical Energy Gap increase fish included accounts optical also calculate the constants visual as factories winding down and the refractive index and reflectivity membranes also by real part and imaginarythe dielectric constant